2006
DOI: 10.1111/j.1741-5705.2006.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Religious Influences in the 2004 Presidential Election

Abstract: In this article, we examine the impact of religious variables on the vote in the 2004 presidential election. First, we review and evaluate two theories that underlie many interpretations of religion’s role in American electoral politics, namely, the ethnoreligious and the religious restructuring perspectives. Using both approaches, we deploy a comprehensive classification incorporating religious affiliations, beliefs, and practices that is quite successful in capturing the electoral impact of religion. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 8 publications
(7 reference statements)
7
100
0
2
Order By: Relevance
“…The one, and possibly only, area of complete consensus in relation to religion and politics in the United States has to do with the fact that white conservative Protestants, now the majority of American Protestants because of their greater fertility nearly a century ago (Hout et al 2001), hold conservative political views and increasingly support the Republican party (Guth et al 2006, Kohut et al 2000, Miller & Hoffmann 1999, Woodberry & Smith 1998). …”
Section: The Current Consensus: (White) Conservative Protestants Are mentioning
confidence: 96%
See 1 more Smart Citation
“…The one, and possibly only, area of complete consensus in relation to religion and politics in the United States has to do with the fact that white conservative Protestants, now the majority of American Protestants because of their greater fertility nearly a century ago (Hout et al 2001), hold conservative political views and increasingly support the Republican party (Guth et al 2006, Kohut et al 2000, Miller & Hoffmann 1999, Woodberry & Smith 1998). …”
Section: The Current Consensus: (White) Conservative Protestants Are mentioning
confidence: 96%
“…Here we focus on studies in which religion is the independent variable and politics the dependent variable (Williams 1996). By "politics," we mean everything from direct political activity, 3 including voting behavior (Brooks & Manza 1997b, Evans 2000, Manza et al 1995 and party affiliation (Guth et al 2006, Kohut et al 2000, Miller & Hoffmann 1999, Woodberry & Smith 1998, to views on politically salient issues (Green et al 2002, Hutchings & Valentino 2004, including of course the "culture wars" debate (Hunter 1991). By necessity, we save for future scholars related topics such as the study of social movements (Davis et al 2010, Wald et al 2005, Wood 1999, Young 2002, Yukich 2013 or political cultures (Berezin 1997) and nationalism (Zubrzycki 2006) and the way they intersect with race, class, and religion.…”
Section: Introductionmentioning
confidence: 98%
“…This effect has been noted most clearly in the American context, where moral conservatives of all religious traditions -notably but not only Catholics and Protestants -have increasingly gravitated toward the Republican Party while liberals of all faiths support the Democrats. The difference in presidential voting between 1960, when religious tradition was key, and 2004, when religious intensity trumped faith tradition, is stark (Guth, Kellstedt, Smidt, & Green, 2006;Wuthnow, 1989).…”
Section: Religiosity and Fertilitymentioning
confidence: 99%
“…Several authors have found significant effects for religious affiliation with the greatest opposition to same-sex marriage coming from Protestants, especially evangelical Protestants, and those identifying themselves as born again (Bramlett 2012;Bushong 2011;Campbell and Monson 2008;Denton Jr. 2005;Drenner 2011;Ellison et al 2011;Guth et al 2006;Hines 2011;McKenzie and Rouse 2013;Miller 2009;Olson et al 2006;Sherkat et al 2010;Sherkat et al 2011). The religious variable with the greatest impact across most of these studies was religious commitment or religiosity.…”
Section: Factors Influencing Opinion On Same-sex Marriagementioning
confidence: 99%